Loss and gain of chromosome 5 controls growth of Candida albicans on sorbose due to dispersed redundant negative regulators - Kabir, M. Anaul (National Academy of Sciences, 2005)
A reversible decrease or increase of Candida albicans chromosome copy number was found to be a prevalent means of survival of this opportunistic pathogen, under conditions that kill cells or inhibit their propagation. The utilization of a secondary carbon source, l-sorbose, by reversible loss of chromosome 5, serves as a model system. We have determined that an ≈209-kbp portion of the right arm of chromosome 5 contains at least five spatially separated, functionally redundant regions that control utilization of l-sorbose. The regions bear no structural similarity among themselves, and four of them contain sequences that bear no similarity with any known sequence. We identified a regulatory gene in region A that encodes a helix-loop-helix protein. Most important, the multiple redundant regulators scattered along chromosome 5 explain, in a simple, elegant way, why the loss of the entire homologue is usually required for growth on sorbose. Thus, an entire chromosome acts as a single regulatory unit, a feature not previously considered. Our finding appears to be a paradigm for the control of other phenotypes in C. albicans that also depend on chromosome loss, thus implying that C. albicans genes are not distributed randomly among different chromosomes.